2008 general elections in Malaysia: democracy at work - Moten, Abdul Rashid (Cambridge University Press, 2009)
The Barisan Nasional (BN) which won a landslide in 2004 was returned to power in 2008 elections with reduced majority and the loss of five state assemblies.Dissatisfied with unfulfilled promises, the electorate protested by voting for a strong opposition. BN additionally was characterized by factionalism. Three opposition parties joined hands and, using alternative media, unexpectedly won 82 seats in the parliament. A strong responsible opposition bodes well for Malaysian democracy.